Measurement of Health Information Systems Using the McCall Method - Dzaki Al Fikri; Yuhandri; Mardison (Universitas Putra Indonesia YPTK Padang, 2024)
In an era of technology that continues to develop rapidly, structured and detailed data management is becoming increasingly important. This allows decision makers at the Clinic to easily monitor, evaluate and plan business strategies. The information system measurement application on Klink Mitra Sadona is used to analyze the quality of the electronic registration information service system for patients. This registration system can help patients make it easier to register at the clinic. Based on this, the quality of the health information system will be measured because in this system the level of system quality is not yet known, so as to identify the accuracy, completeness and quality of the software at the clinic. The measurement method in this research uses the McCall Method. The McCall method is a method used to assess the quality of a system. The results of research based on the McCall Method show that the quality of information system measurements is very good with a percentage value of 94%, with the best indicator value, namely efficiency with a result of 72% and the integrity indicator value is the worst indicator with a result of 52%.